Documents and statements respecting the sulphur monopoly, constituting grounds for parliamentary inquiry into the conduct of the Foreign Secretary (Reid, 1841)
Contains among other things The sulphur question / by William Cargill ; Analysis of Parliamentary Papers on the sulphur monopoly / by David Urquhart.